2022
DOI: 10.1111/1346-8138.16415
|View full text |Cite
|
Sign up to set email alerts
|

Severe graft‐versus‐host disease‐like enterocolitis accompanied with cytomegalovirus‐reactivation in drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms

Abstract: Drug‐induced hypersensitivity syndrome (DIHS)/drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe drug adverse reaction with skin eruption and visceral organ involvement. The characteristic clinical features of DIHS/DRESS are reactivation of human herpesviruses (HHV) and the development of autoimmune diseases, but their pathogenesis and associations are not yet understood. Here, we report a 66‐year‐old man who presented with fever, generalized erythema, diffuse lymphadenopathy, and diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Multi-organ system involvement have been reported with evidence of HHV-6 reactivation within specific organ parenchyma or in serum, sometimes leading to fatal sequelae related to the liver, 12 - 19 kidney, 7 , 12 , 20 - 23 gastrointestinal tract, 24 , 25 bone marrow, 12 , 26 - 28 lymph nodes, 12 , 29 , 30 peripheral and central nervous system, 7 , 31 - 34 heart, 13 , 35 and lung. 36 , 37 There have been many reports of new-onset autoimmune disease, as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-organ system involvement have been reported with evidence of HHV-6 reactivation within specific organ parenchyma or in serum, sometimes leading to fatal sequelae related to the liver, 12 - 19 kidney, 7 , 12 , 20 - 23 gastrointestinal tract, 24 , 25 bone marrow, 12 , 26 - 28 lymph nodes, 12 , 29 , 30 peripheral and central nervous system, 7 , 31 - 34 heart, 13 , 35 and lung. 36 , 37 There have been many reports of new-onset autoimmune disease, as well.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of HHV-6 playing an exacerbating role in both conditions has not been ruled out, as demonstrated by a case of DRESS complicated by GVHD enterocolitis. 25 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, STAT1 , ISG15 , and SCN2B were found to interact with garcinol and ipriflavone, as well as irinotecan and zonisamide, respectively. Interestingly, recent studies have shown that garcinol and ipriflavone have anti-inflammatory effects, especially in the inflammation of the brain 35 38 , while irinotecan and zonisamide can induce inflammation 39 42 . Therefore, STAT1 , ISG15 , and SCN2B may be new targets for HIVE drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Herpesviridae reactivation has also been reported in the progression of the disease 15 . However, whether the viral reactivation is a cause or solely a consequence of DRESS syndrome has yet to be elucidated 16,17 . HHV‐6 is the most common virus associated with DRESS, with reactivation reported in 16 to 60% of cases 3,15 …”
Section: Discussionmentioning
confidence: 99%
“…15 However, whether the viral reactivation is a cause or solely a consequence of DRESS syndrome has yet to be elucidated. 16,17 HHV-6 is the most common virus associated with DRESS, with reactivation reported in 16 to 60% of cases. particular features distinguish this syndrome from others.…”
Section: Etiologymentioning
confidence: 99%